HNF1α Controls Liver Lipid Metabolism and Insulin Resistance via Negatively Regulating the SOCS-3-STAT3 Signaling Pathway. (15th May 2019) - Tan, Jiaorong; Xu, Jiahong; Wei, Guohua; Zhang, Lijuan; Sun, Long'e; Wang, Guangyu; Li, Fei; Jiang, Fengxiang
Abstract : This study is aimed at evaluating the effects, functions, and mechanism of HNF1 α on hepatic glycolipid metabolism. In this study, free fatty acid- (FFA-) induced steatosis of hepatocyte liver cell LO2 was used as an in vitro model. The methods of Oil Red O staining, RT-qPCR, western blot, and immunofluorescence staining were used to detect LO2-regulated HNF1 α expression and its effects on FFA-induced LO2 cell steatosis, the insulin signaling and SOCS-3-STAT3 signaling pathways, the expression of lipid metabolism-related regulators, and phosphorylation. With increased FFA induction time, the expression of HNF1 α in the LO2 fatty degeneration hepatic cells gradually decreased. Downregulation of HNF1 α expression aggravated FFA-induced steatosis of LO2 hepatocytes. HNF1 α promotes activation of the insulin pathway and oxidative breakdown of fat and inhibits lipid anabolism. Inhibitors of STAT3 can reverse the regulation of decreased HNF1 α expression on the insulin signaling pathway and fat metabolism. We also confirmed this pathway using HNF1 α -/- mice combining treatment with STAT3 inhibitor NSC 74859 in vivo . HNF1 α regulates hepatic lipid metabolism by promoting the expression of SOCS-3 and negatively regulating the STAT3 signaling pathway.